A cell-based model to study mechanisms of endothelial-dependent thrombin generation in response to inflammation and its modulation by hydroxychloroquine - Deepa J. Arachchillage; Golzar Mobayen; Mike Laffan; Anna M. Randi; Josefin Ahnström; Charis Pericleous (Research and Practice in Thrombosis and Haemostasis)
Background: Inflammation is a driver of thrombosis, but the phenomenon of thromboinflammation has been defined only recently, bringing together the multiple pathways involved. In vitro models can support the development of new therapeutics targeting the endothelium and also assess the existing immunomodulatory drugs, such as hydroxychloroquine, in modulating the inflammation-driven endothelial prothrombotic phenotype. Objectives: To develop a model for thrombin generation (TG) on the surface of human endothelial cells (ECs) to assess pro/antithrombotic properties in response to inflammation. Furthermore, to elucidate the mechanisms of TG regulation and its modulation by immunomodulatory therapies. Methods: Cytokine-induced (tumor necrosis factor [TNF]-α, interleukin [IL]-1β, and interferon-γ) effects on ECs isolated from umbilical veins or human aortic tissue were assessed using calibrated automated thrombography in platelet-poor plasma. The expression of key coagulant and inflammatory regulators was measured at the mRNA level. Tissue factor (TF) protein levels were further assessed by flow cytometry. Results: Endothelial stimulation with TNF-α or IL-1β caused ECs to trigger TG without the addition of exogenous TF, with higher TG observed after 6 hours of stimulation than 24 hours. IL-1β induced higher peak thrombin (170 ± 5.9 nM vs 115 ± 4.9 nM), endogenous thrombin potential (1632 ± 35 nM ∗ min vs 1370 ± 23 nM ∗ min) presented as mean ± SD, and TF expression (∼2.8-fold higher) compared with TNF-α at 6 hours. Interferon-γ stimulation failed to induce TG and TF expression. The immunomodulatory drug, hydroxychloroquine, reduced cytokine-induced TG and downregulated TF expression. Conclusion: We provide detailed optimization of a robust in vitro model to assess the induction of an inflammation-driven endothelial prothrombotic phenotype that is also sensitive to immunomodulatory therapies, providing a tool for investigating mechanisms of disease and new drugs.